ANALISIS MISKONSEPSI PESERTA DIDIK MENGGUNAKAN FOUR TIER DIAGNOSTIC TEST PADA MATERI PERPINDAHAN KALOR - Rahayu, Eva Putri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to describe students' misconception profiles on the heat transfer material. Descriptive quantitative research is the focus of this kind of study. This study's participants were all Class VII students at SMPN 21 Pontianak during the 2022/2023 school year. In this study, a purposive sampling technique was used, which means that the researcher set specific criteria or considerations for the sampling. A diagnostic test-based measurement technique is utilized for data collection. A nine-question four-tier diagnostic test was the research instrument used in this study. The findings demonstrated that there were misconceptions regarding heat transfer materials in both classes VII C and VII E. In class VII C, the highest misconception was found in indicator I, namely identifying the process of heat transfer by conduction. Whereas in class VII E the highest misconceptions were found in indicators II and III, namely identifying heat transfer processes by convection and radiation. The Mann-Whitney U test results demonstrate that the sig. 0.05, which indicates that the number of misconceptions in classes VII C and VII E is not significantly different.  This indicates that the two classes begin with the same set of circumstances that is, they both have misconceptions.